THE ESSENCE AND PECULIARITIES OF ADMINISTRATIVE LIABILITY IN UKRAINE - Butenko, Artem (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this study is to substantiate the essence and peculiarities of administrative liability, to analyse its legal nature, and also to determine the possibilities and the need to improve the procedural framework for bringing to administrative liability. The methodological basis of the article is a set of methods and techniques of scientific cognition - dialectical, systemic, logical, comparative, functional - for generalising the material of its analysis and substantiating the conclusions. Results: the conclusions proposed by the author may be used in the process of further elaboration of the issues related to ensuring the legality of administrative liability. In law enforcement activities, the conclusions may become a guideline in the process of amending the administrative and tort legislation of Ukraine, updating the legislator’s approaches to determining the legal personality of participants to proceedings on administrative offences. Many entities, both state bodies (officials) and public bodies and their officials, are empowered to consider cases of administrative offences. At the same time, many officials who apply administrative penalties do not have a legal education. At the same time, the Constitution of Ukraine defines the rights and freedoms of man and citizen, and their honour and dignity are the highest value. That is why they and their guarantees need to be protected. Of course, this also applies to legislation on administrative offences, which should provide for an appropriate mechanism to protect the rights and freedoms of citizens. The application of any state influence on offenders must be carried out on a legal basis, i.e., regulated by the norms of the current legislation of Ukraine. Expanding the scope of administrative liability in the legal aspect, a wide range of subjects of administrative liability, the frequency of application of this type of state coercion in order to protect public relations, a large number of subjects exercising administrative liability and frequent abuse by these subjects, imperfection of the provisions of Ukrainian legislation on administrative liability make it necessary to improve the administrative and tort legislation of the State. Expanding the scope of administrative liability in the legal aspect, a wide range of subjects of administrative liability, the frequency of application of this type of state coercion in order to protect public relations, a large number of subjects exercising administrative liability and frequent abuse by these subjects, imperfection of the provisions of Ukrainian legislation on administrative liability make it necessary to improve the administrative and tort legislation of the State. This should be taken into account, first and foremost, in the process of drafting a new Code of Ukraine on Administrative Offences and adopting this codified legal act in Ukraine.